Deindustrialisation and the long term decline in fatal occupational injuries. Issue 7 (18th June 2004) - Loomis, D; Richardson, D B; Bena, J F; Bailer, A J
Abstract : Aims: To examine the extent to which deindustrialisation accounts for long term trends in occupational injury risk in the United States. Methods: Rates of fatal unintentional occupational injury were computed using data from death certificates and the population census. Trends were estimated using Poisson regression. Standardisation and regression methods were used to adjust for the potential effect of structural change in the labour market. Results: The fatal occupational injury rate for all industries declined 45% from 1980 to 1996 (RR (rate ratio) 0.55, 95% CI 0.52 to 0.57). Adjustment for structural changes in the workforce shifted the RR to 0.62 (95% CI 0.60 to 0.65). Expanding industries enjoyed more rapid reduction in risk (−3.43% per year, 95% CI −3.62 to −3.24) than those that contracted (−2.65% per year, 95% CI −2.88 to −2.42). Conclusions: Deindustrialisation contributed to the decline of fatal occupational injury rates in the United States, but explained only 10–15% of the total change.